2015
DOI: 10.4103/2347-5625.146223
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors with cervical pre-malignant lesions among the married fisher women community at Sadras, Tamil Nadu

Abstract: Objective:To identify the associated factors of cervical pre-malignant lesions among the married fisher women residing in the coastal areas of Sadras, Tamil Nadu.Methods:The study was conducted in five fishermen communities under Sadras, a coastal area in Tamil Nadu, India. Two hundred and fifty married fisher women residing in the area. Quantitative descriptive approach with a cross-sectional study design was used. Data were collected using a structured interview schedule for identifying the associated factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…Similar findings have also been reported by Rajput et al [2]. Ganeshan et al [16] also found advance age to be a significant risk factor for the development of precancerous lesions of the cervix in coastal women of Tamil Nadu.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings have also been reported by Rajput et al [2]. Ganeshan et al [16] also found advance age to be a significant risk factor for the development of precancerous lesions of the cervix in coastal women of Tamil Nadu.…”
Section: Discussionsupporting
confidence: 88%
“…However, a very low incidence of SIL in rural screenings (0.9%) was found by Nene et al [14]. A rate of 0.3% was reported by Nikumbh et al [15] in rural Maharashtra, and a rate of 0.4% was found by Ganeshan et al [16] in coastal area of Tamil Nadu.…”
Section: Discussionmentioning
confidence: 95%
“…The results of several studies suggest that socioeconomic differences play an important role in the incidence, mortality and survival rate of cervical cancer (Akinyemiju et al, 2016;Ibfelt et al, 2013;Kim and Kang, 2016;Ueda et al, 2006). This is associated with a variety of factors, such as low access to screening (Leinonen et al, 2017), non-implementation of prevention programs (Chidyaonga-Maseko et al, 2015), ineffective and inadequate treatment, and poor sanitary conditions (Benard et al, 2008;Ganesan et al, 2015;Rossi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly a study among fisherwomen communities in Indian, documented, advanced age, lack of education, low socioeconomic status multiparty among others as factors increasing vulnerability to cervical cancer. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%